The incidence of drug abuse in unnatural deaths in Northern Thailand - Paitoon Narongchai (2018)
Objective: Study the incidence of drug abuse in persons with unnatural deaths such as traffic accidents, homicide with gunshot wounds, etc. Material and Method: One hundred and fifty three cases with a mean age of 34 years (range 10 to 76) were studied. The decedents were mostly male (92%), with a variety of occupations including laborers (76.9%), traders (15.4%), and student(7.7%). The causes of death were mainly traffic injuries (33%), gunshot wounds (26%) and others (stab wound, poisoning, asphyxia etc 41%). The manner of death was accidents in 40% and homicides in 28%. Results: Nine percent were positive for methamphetamine or amphetamine derivatives. Tests for Heroin, 6-MAM, morphine, or cocaine were also performed but not detected. The drug positive cases were mostly males (85%) with the most common age range of 21-30 years (35.4%) and 61% with only primary education. Homicide by gunshot wounds was the most common cause of death at 69.2%, followed by hanging (15.4%), electrocution (7.7%), and poisoning (7.7%). The concentration of methamphetamine in urine was between 501 - 61,147 ng/ml, which cannot be correlated with intoxication. There were no deaths from overdose. Three Benzodiazepine, one toluene, and one meperidine cases were also found in cases of methamphetamine abuse. Alcohol was found mostly in the persons with unnatural deaths (53.6%) from traffic accidents. Conclusion: This information helps us understand the marketing strategies, and the trading routes. All data will be used for planning to eradicate these drugs from Thailand in line with government strategies.